From Logical Structure to Critical Reasoning: Philosophical Perspectives on Venn Diagrams as Epistemological Tools - Ahmad, Andi Kamal; Nurcholish Aziz; Marjuni; Afifuddin Harisah; Muhammad Amin (Journal of Practice Learning and Educational Development, 2026)
This paper addresses the research gap where the Venn Diagram is narrowly viewed as a technical tool in set theory, overlooking its profound philosophical role in logic. By employing a qualitative literature review that synthesizes classical philosophical texts on logic with contemporary mathematical analysis, the study aims to recontextualize the Venn Diagram as a critical epistemological instrument for valid reasoning. The methodology focuses on integrating foundational principles of philosophy with the diagram's procedural mechanics. The analysis reveals that the systematic notation of the Venn Diagram (shading for null sets and 'x' for existential import) provides a formal, visual procedure for testing the validity of syllogistic arguments. This process effectively transforms abstract logical structures into a tangible "visual logic," enhancing both problem-solving capabilities and the philosophical pursuit of rigor and clarity. In conclusion, this recontextualization successfully demonstrates the Venn Diagram’s function as a crucial bridge between abstract logic and concrete critical thinking, suggesting the need to reinforce the teaching of such visual-logical tools within broader philosophical and educational frameworks to cultivate robust moral and critical reasoning.